2016
DOI: 10.3390/molecules21060721
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Silverskin Extract Protects against Accelerated Aging Caused by Oxidative Agents

Abstract: Nowadays, coffee beans are almost exclusively used for the preparation of the beverage. The sustainability of coffee production can be achieved introducing new applications for the valorization of coffee by-products. Coffee silverskin is the by-product generated during roasting, and because of its powerful antioxidant capacity, coffee silverskin aqueous extract (CSE) may be used for other applications, such as antiaging cosmetics and dermaceutics. This study aims to contribute to the coffee sector's sustainabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 49 publications
3
29
0
1
Order By: Relevance
“…On the other hand, the tested concentrations of CS extracts were not cytotoxic, and a CS extract of 1 mg/mL gave resistance to skin cells when oxidative damage was induced by t-BOOH. According to the authors, the anti-aging properties of CS may be due to its complex mixture of antioxidants that act in a synergistic combination [33]. In sum, CS extracts have the potential to be used as an ingredient in skin cosmetic product to reduce the production of intracellular ROS in keratinocytes and improving skin health.…”
Section: Anti-aging Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the tested concentrations of CS extracts were not cytotoxic, and a CS extract of 1 mg/mL gave resistance to skin cells when oxidative damage was induced by t-BOOH. According to the authors, the anti-aging properties of CS may be due to its complex mixture of antioxidants that act in a synergistic combination [33]. In sum, CS extracts have the potential to be used as an ingredient in skin cosmetic product to reduce the production of intracellular ROS in keratinocytes and improving skin health.…”
Section: Anti-aging Activitymentioning
confidence: 99%
“…A new approach on anti-aging effect of CS extracts against accelerated aging caused by oxidative agents, was performed by Iriondo-DeHond et al [33]. In this study, accelerated aging in C. elegans (animal model) was induced by ultraviolet radiation C (UVC) and in HaCaT cells (skin model) using tert-butyl hydroperoxide (t-BOOH).…”
Section: Anti-aging Activitymentioning
confidence: 99%
“…The results suggested that coffee silverskin extract protects the human keratinocytes from oxidative damages and extends the lifespan of Caenorhabditis elegans [19]. Rodrigues et al [20] proved that coffee silverskin was a cosmetically significant candidate with high antioxidant and antimicrobial property with no cytotoxicity to human cells.…”
Section: Resultsmentioning
confidence: 99%
“…While ROS are excessively generated and exceed the ability of organism anti-oxidation the body will be in oxidative stress, which leads to a sharp deterioration of many bodily functions such as a gradual deterioration in learning and memory capacity and acceleration of apoptosis levels in the brain. 36 There are numerous endogenous antioxidants (SOD, GSH-Px, and CAT) that constitute the body's own natural defense systems and keep a certain balance with ROS to limit free radical damage in neuronal tissues. 37 The oxidative stress damage increases in aging, mainly because of anti-oxidation deciency.…”
Section: Discussionmentioning
confidence: 99%